[13C3, 15N1]-labeled isodesmosine: A potential internal standard for LC–MS/MS analysis of desmosines in elastin degradation. Issue 10 (15th May 2015) - Tanigawa, Takahiro; Komatsu, Akira; Usuki, Toyonobu
Graphical abstract: Abstract: Isodesmosine and desmosine are crosslinking amino acids that are present only in elastin. They are useful biomarkers for the degradation of elastin, which occurs during the progression of chronic obstructive pulmonary disease (COPD) and related diseases. This Letter describes the synthesis of [ 13 C3, 15 N1 ]-labeled isodesmosine, using Chichibabin pyridine synthesis as a key reaction. The labeled isodesmosine is a potential internal standard for the quantitative LC–MS/MS analysis of desmosines in elastin degradation.